The efficacy and safety of minocycline as adjuvant therapy in refractory mycoplasma pneumonia in Chinese children: a meta-analysis - Hong-Xia Shen; Chang Liu; Hui-Jun Lin; Lu-Jie Xu; Guang-Yan Wang; Mei-Xing Yan (BMC, 2022)
Abstract Background To explore the efficacy and safety of minocycline as adjuvant therapy for refractory mycoplasma pneumonia in Chinese children. Methods PubMed, EMBASE, Cochrane Library, CNKI, Wanfang database and VIP database were systematically searched. Studies where minocycline was used as adjuvant therapy for refractory mycoplasma pneumonia in Chinese children were included. The effect of numeration data and the measurement data were represented by odds ratios (OR) and weighted mean differences (MD), respectively. Review Manager version 5.3 was used to compare the treatment efficacy, time for the cough to subside, defervescence time, hospitalisation time, adverse events and other indicators. Results Ten studies involving 857 patients were included in the final analysis. Compared with the conventional treatment of refractory mycoplasma pneumonia in children, the addition of minocycline as adjuvant therapy was found to improve the treatment efficacy (OR: 5.45; 95% CI: 3.46, 8.57, p < 0.001); shorten the duration of cough (MD: -3.61; 95%CI: -4.25, -2.97, p < 0.001), fever time (MD: -4.77; 95% CI: -6.30, -3.23, p < 0.001) and hospitalisation time (MD: -5.53 (95% CI: -7.19, -3.88, p < 0.001); and decrease the concentration of C-reactive protein (MD: -13.95; 95%CI: -18.61, -9.29; p < 0.001) and the erythrocyte sedimentation rate (MD: -10.88; 95% CI: -14.05, -7.72, p < 0.001). The use of minocycline did not lead to significant adverse events (OR = 0.63; 95% CI: 0.39, 1.01, p = 0.05). Conclusion The use of minocycline as adjuvant treatment of refractory mycoplasma pneumonia in Chinese children has good efficacy and safety and may be promoted in clinical practice.